Design of control laws and state observers for fixed-wing UAVs : simulation and experimental approaches /: simulation and experimental approaches. (2022) - Espinoza-Fraire, Arturo Tadeo; Dzul, Alejandro E; Morado, Ricardo Pavel Parada; Esqueda, Jose Armando Saenz
No abstract available